The actuator farm model for large eddy simulation (LES) of wind-farm-induced atmospheric gravity waves and farm–farm interaction - S. Stipa; A. Ajay; J. Brinkerhoff (Wind Energy Science)
This study introduces the actuator farm model (AFM), a novel parameterization for simulating wind turbines within large eddy simulations (LESs) of wind farms. Unlike conventional models like the actuator disk (AD) or actuator line (AL), the AFM utilizes a single actuator point at the rotor center and only requires two to three mesh cells across the rotor diameter. Turbine force is distributed to the surrounding cells using a new projection function characterized by an axisymmetric spatial support in the rotor plane and Gaussian decay in the streamwise direction. The spatial support's size is controlled by three parameters: the half-decay radius r1/2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="27f1caa887926dd8dce18530ebf900c8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wes-9-2301-2024-ie00001.svg" width="20pt" height="12pt" src="wes-9-2301-2024-ie00001.png"/></svg:svg>, smoothness s, and streamwise standard deviation σ. Numerical experiments on an isolated National Renewable Energy Laboratory (NREL) 5MW wind turbine demonstrate that selecting r1/2=R<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="40pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="4f7e0481fb859c228ed057d5eb4a8cc5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wes-9-2301-2024-ie00002.svg" width="40pt" height="14pt" src="wes-9-2301-2024-ie00002.png"/></svg:svg> (where R is the turbine radius), s between 6 and 10, and σ≈Δx/1.6<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="513419cf9f56555a3167718d25d80d91"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="wes-9-2301-2024-ie00003.svg" width="58pt" height="14pt" src="wes-9-2301-2024-ie00003.png"/></svg:svg> (where Δx is the grid size in the streamwise direction) yields wake deficit profiles, turbine thrust, and power predictions similar to those obtained using the actuator disk model (ADM), irrespective of horizontal grid spacing down to the order of the rotor radius.